Analysis of Factors Related to Malaria Disease In Intan Jaya, Papua - Laangka, Muliyati; Muli (Journal of Epidemiology and Health Science, 2026)
Background : Malaria is one of the public health problems that is still a concern in endemic areas such as Intan Jaya Regency, Papua. Environmental factors and community behavior are thought to play an important role in supporting or inhibiting the spread of this disease. Therefore, an understanding of the various risk factors that influence the incidence of malaria is essential to determine the right preventive measures. Objective: The purpose of this study was to identify and analyze factors related to malaria incidence in the working area of Wandai Health Center, Wandai District, Intan Jaya Regency, Papua through a literature review approach. Methods: This study used a literature review method from several journal sources relevant to the topic of malaria, especially in endemic areas. Data were reviewed based on variables such as the presence of livestock pens, mosquito breeding sites, habits of using mosquito nets, and habits of going out at night, and analyzed by comparing the results of statistical tests in each study. Results: The results of the review showed that there was a significant relationship between the presence of mosquito breeding sites, the habit of using mosquito nets, and the habit of going out at night with the incidence of malaria. Meanwhile, the presence of livestock pens did not show a significant relationship with the increase in malaria cases. Conclusion: Malaria in Intan Jaya Regency, Papua is influenced by a combination of environmental and behavioral factors, especially related to mosquito breeding sites and community activities at night. Malaria control efforts must focus on behavioral interventions and improving the environmental conditions of people's homes. Keywords : Malaria, community behavior, environment, anopheles mosquitoes.